Perlindungan Hak Konsumen Pada Penggunaaan E-Commerce: Perspektif Hukum Syariah Islam - Thorik, Achmad; Putri Suryan, Widaningrum; Kirana Putri, Al-Zahra; Tri Andini, Lulu (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2023)
In Indonesia , there is a Consumer Protection Law as an effort to guarantee consumer protection in online transactions, especially in e-commerce. This research aims to examine muamalah's legal views regarding consumer rights amidst the widespread use of e-commerce. This research is normative legal research which includes a statutory approach (statue approach) and a case approach, which in obtaining legal materials is carried out through literature study. Based on the research results, it is known that the practice of e-commerce in the business world is seen as a form of digitalization of buying and selling which according to Islamic sharia is permitted provided that it follows sharia principles and applicable legal regulations, especially in fulfilling consumer rights and protection. Researchers will examine Islamic legal views on e-commerce transactions and find out how consumer rights are fulfilled in the e-commerce system.